'The Mortar Between the Bricks': Willis Conover and Global Jazz. (1st September 2017) - Buck, Brandan P.
ABSTRACT: Willis Conover was arguably the most famous American in the pre-internet age. This Voice of America radio program, Music U.S.A . beamed popular music and jazz into people's lives all over the world from 1956 to his death in 1996. His program was part of a broader effort on the part of the US government to use jazz as diplomatic tool in their struggle against communism. This paper argues that Willis Conover's Music U.S.A . became the "mortar between the bricks" of the globalized jazz community, a cultural medium which simultaneously served US foreign policy interests, furthered the spread of jazz and fostered communication between physically and ideologically separated peoples. Conover achieved because his program was the nexus between uninterrupted government support, the power of mass radio and commercialized recording companies. This paper makes use of varied sources to include US government documents, Conover's personal papers, periodicals, fan letters, production materials as well as oral histories and contemporary interviews.